State Security from the Perspective of Selected Gaps in the System of Classified Information Protection - Zapart, Robert (Roczniki Nauk Społecznych, 2025)
The paper analyses threats to state security resulting from the visible shortcomings of the Protection of Classified Information Act and the practice of its application until now. The author also offers solutions that eliminate or limit the risk of security breaches. The research questions address the causes of such risks and their repercussions, which are connected with the relativization of protection rules, including the objectionable freedom in granting and revoking confidentiality clauses and conducting security clearance proceedings without the supervision of independent bodies, and the limitation of public control over entities responsible for the classified information protection system. The paper argues that this requires an amendment of the cited legal norm in the face of new challenges and threats to state security.